A European randomised controlled trial for venous leg ulcers: A mathematical model analysis - Renner, Regina (Journal of Wound Care, 2020)
CRIS-Team Scopus Importer:2020-11-27

Comorbidity and Therapeutic Approaches in Patients with Necrobiosis Lipoidica - Erfurt-Berge, Cornelia; Heusinger, Veronika; Reinboldt-Jockenhöfer, Finja; Dissemond, Joachim; Renner, Regina (Dermatology, 2021)
Background: Necrobiosis lipoidica (NL) is a rare granulomatous disorder of unknown aetiology. Randomized controlled studies are not available due to it being an orphan disease. Objectives: We evaluated patients in 2 dermatological centres to cluster data about epidemiology, the therapeutic approaches for NL, and their efficacy. Materials and Methods: Comorbidity and the efficacy of the applied treatment was assessed for 98 patients. Results: We identified 54% of patients with concomitant diabetes and 19% with thyroidal disorders. Topical steroids (85.7%) were predominantly used followed by calcineurin inhibitors (31%) and phototherapy (41.8%). Systemically, fumaric acid esters were more frequently applied (26.8%) than steroids (24.4%) and dapsone (24.4%). Steroids, compression therapy, calcineurin inhibitors, phototherapy, fumaric acid esters, and dapsone showed remarkable efficacy. Conclusion: Therapeutic options were chosen individually in accordance with the severity of NL and presence of ulceration. Topical calcineurin inhibitors, systemic application of fumaric acid esters, and dapsone represent effective alternatives to the use of steroids.
CRIS-Team Scopus Importer:2021-04-19

Development and evaluation of an interprofessional teaching concept for modern wound management - Bergendahl, Lukas; Werner, Felix; Schmidt, Anita; Ronicke, Moritz; Renner, Regina; Erfurt-Berge, Cornelia (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
Background and objectives: The aim of the present study was to establish and evaluate a new interprofessional teaching concept on the topic of wound management. Methods: After determining the status quo using a survey among medical students, we developed a new teaching concept that included a 150-minute course aimed at providing students with the opportunity to gain hands-on wound management skills. This interprofessional course was offered at the existing ‘SkillsLab’ teaching facility. The participants’ subjective level of knowledge was assessed by questionnaire before and after the course. Results: Our survey among 190 medical students showed them to be very interested in gaining practical experience in the field of wound management. To date, 120 participants (54.8 % medical students; 45.2 % nursing students) have attended this new interprofessional course, which has been equally well received by both medical and nursing students. For all specific topics (diagnosis, treatment, use of wound dressings, debridement), course participation was associated with a significant increase in knowledge. Conclusion: Given its relevance in clinical practice, it is important for medical students to learn about the various aspects associated with the care of patients with chronic wounds. By offering new teaching concepts, dermatology in particular is well suited to help students gain a better understanding of the challenges related to wound management and to improve their practical skills. Wound management is an ideal topic for interprofessional learning.
CRIS-Team Scopus Importer:2020-09-11

Entwicklung und Evaluation eines interprofessionellen Lehrkonzepts zum modernen Wundmanagement - Bergendahl, Lukas; Werner, Felix; Schmidt, Anita; Ronicke, Moritz; Renner, Regina; Erfurt-Berge, Cornelia (Journal der Deutschen Dermatologischen Gesellschaft, 2020)
CRIS-Team Scopus Importer:2020-10-09

Interdisciplinary Approach to Diagnostic and Therapy of Ulcus cruris - Erfurt-Berge, Cornelia; Renner, Regina (Aktuelle Dermatologie, 2021)
Eine chronische Wunde am Unterschenkel ist in der dermatologischen Ambulanz ein haufig gesehenes Krankheitsbild. Dennoch stellen Diagnostik und Therapie eine Herausforderung dar, denn es sind nicht nur die vaskularen, sondern auch die selteneren Differenzialdiagnosen, die es fruhzeitig zu erkennen und kausal zu therapieren gilt, wobei der Dermatologe oft erster konsiliarischer Ansprechpartner anderer Fachdisziplinen ist.
CRIS-Team WoS Importer:2021-03-12

Interdisciplinary Approach to the Diagnosis and Treatment of Leg Ulcers - Erfurt-Berge, Cornelia; Renner, Regina (Phlebologie, 2022)
CRIS-Team WoS Importer:2022-12-30

Management of patients with calciphylaxis: current perspectives - Erfurt-Berge, Cornelia; Renner, Regina (Chronic Wound Care Management and Research, 2019)
Calciphylaxis (CP) is a rare disorder presenting with painful ischemic skin ulcerations. Its association with end-stage renal disease, but also non-uremic cases have been described. Several risk factors, like metabolic syndrome, calcium-phosphate imbalance, anticoagulative medication and female gender have been discussed. Multidisciplinary therapeutic approaches are necessary since evidence-based guidelines are missing due to lack of pathophysiological understanding of the disease and the absence of studies with large patient cohorts. However, strategies for local wound therapy, reduction of risk factors and systemic therapies are being developed. Changes in duration, frequency and method of hemodialysis and specific medication to lower the calcium upload can be effective in uremic CP cases. Systemic treatments with cinacalcet, sodium thiosulfate or bisphosphonates have been applied successfully in CP patients, but large placebo-controlled randomized trials are still needed to gather better insight into this fatal disease.
CRIS-Team WoS Importer:2019-10-25

Nutrition status in patients with wounds: a cross-sectional analysis of 50 patients with chronic leg ulcers or acute wounds - Renner, Regina; Garibaldi, Melina Da Silva; Benson, Sven; Ronicke, Moritz; Erfurt-Berge, Cornelia (European Journal of Dermatology, 2019)
Background: The possible impact of nutritional status on healing and course of disease in patients with chronic wounds is widely suggested, however, most data are based on small groups of patients with no control group and minor afflictions. Clear diagnostic strategies are missing. Objectives: To analyse in detail the nutritional status of chronic wound patients relative to healthy controls based on a large patient population. Material and Methods: We screened a group of 50 patients for their nutritional status based on body mass index (BMI), the Mini-Nutritional Assessment (MNA), and Nutritional Risk Screening (NRS), as well as additional laboratory investigations. Twenty-five patients suffered from chronic venous leg ulcers and were compared with a matching control group of 25 patients with acute surgical wounds. Results: Patients with chronic venous leg ulcers showed significantly higher BMI, hyperhomo-cysteinaemia, and higher levels of serum copper but significantly lower levels of vitamin B6, B9 and C, as well as a significantly lower level of zinc. Vitamin D deficiency was present in both groups, however, severe vitamin D deficiency was present only in the leg ulcer group. Mobility was significantly reduced in patients with leg ulcers. Conclusion: Ulcer patients are often obese but suffer from qualitative malnutrition, including a lack of vitamin D, which might be explained by reduced mobility and being housebound. Hypoalbuminaemia, as a sign of protein deficiency, was observed significantly more often in patients with chronic leg ulcers, irrespective of wound area or wound duration.
CRIS-Team WoS Importer:2020-02-14

Quality of life assessment in family members of patients with chronic wounds - Erfurt-Berge, Cornelia; Ronicke, Moritz; Richter-Schmidinger, Tanja; Walther, Felix; Renner, Regina (European Journal of Dermatology, 2019)
Familial caregivers are often directly involved in treatment of patients with chronic wounds, however, less is known about their personal impairment, and specific support is lacking for these important members of the therapeutic team regarding wound care. The aim of this study was to investigate the influence of wound care provided by family members on their quality of life, and to create a suitable questionnaire to describe the affected personal aspects. A five-part questionnaire, named ELWA, was created by the authors and answered by 30 familial caregivers of 30 respective patients with chronic leg ulcers. One third of the caregivers reported receiving no medical advice about detailed wound care at all. A lack of information regarding details of the disease correlated with personal strain. Additional costs, anxiety, frustration, and reduced spare-time activities were among the top-rated factors affecting quality of life of family members. The results from this newly created questionnaire point out the needs of familial caregivers of patients with chronic wounds and may help to establish individual support. Implementation of clinical treatment strategies is planned through multicentre application.
CRIS-Team Scopus Importer:2019-12-13
Keywords: chronic wounds; family member; leg ulcer; quality of life; wound care

Quality of life in patients with chronic wounds Lebensqualität bei Patienten mit chronischen Wunden - Erfurt-Berge, Cornelia; Renner, Regina (Hautarzt, 2020)
The quality of life of patients with chronic wounds is significantly reduced. Through pain, wound odor, and exudate, they experience limitations in various areas of their daily life. Pain can lead to reduced mobility, sleep disorders, or reduced food intake. Physical limitations caused by the wound itself, dependence on caregivers, and the financial burden are further influencing factors. At the same time, chronic wounds lead to changes in social life, withdrawal from friends and family, and a feeling of powerlessness over a patient’s own life. Pre-existing anxiety or a depressive disorder can further negatively influence the quality of life. There are various general and diagnosis-specific assessment tools for measuring the quality of life of patients with chronic wounds. Such a survey should be carried out regularly in the course of wound therapy. Especially at the beginning of treatment, it is important to identify limiting factors and to evaluate them regularly during wound therapy and to work out possible solutions together with the patient.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Assessment tools; Interventions; Needs assessment; Pain; Physician-patient discussions

Versorgungszustand von Patienten vor Zuweisung an ein universitäres Wundzentrum - Erfurt-Berge, Cornelia; Michler, Melanie; Renner, Regina (Hautarzt, 2021)
Background and objectives: Health care for patients with chronic wounds is often protracted. This can result in decreased quality of care or delayed diagnosis of the actual cause of disease. Concurrently, there are already certified facilities for these patients. The present work investigates possible reasons for delayed referral and whether a specific selection of patients is sent to these university-based centres. Patients and methods: A retrospective patient data chart review at the point of first admission to the certified wound centre was performed to identify concerning variables about the standard of care before university presentation. Results: Records of 177 patients were analysed (53% women, 47% men; patient age range 27–95 years). The mean duration of the wound was 22 months. Vascular diagnostics had already been performed in 32% (arterial diagnostics) and 36% (phlebological diagnostics), respectively. A tissue sample had been analysed in 9% of cases, especially when wound duration exceeded > 24 months. In only 45% of cases was the external diagnosis in accord with the final diagnosis in the wound centre. Discussion: The health care situation for patients with chronic wounds outside of specialised care structures is insufficient. Early and standardized diagnostics and therapy and a reasonable admission to specialised centres is desired.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Basic diagnostics; Care structure; Leg ulcer; Primary care; Quality of care